Henderson and Meyer in correspondence: a transatlantic history of dynamic psychiatry, 1908–29. Issue 1 (March 2017) - Morrison, Hazel
Charting a transatlantic movement of so-called 'dynamic psychiatry' during the early twentieth century, this paper reads against the grain of established historiographies. Comparing biographical and autobiographical sources with contemporary correspondence, a history is told which considers the evolution of psychiatric knowledge and clinical practices 'from below'. Revealing a period and place when a 'dynamic' counter-culture challenged the established materialist views of Scottish psychiatry, the longevity of this challenge is considered in the concluding paragraphs.